Factors related to primary cancer death and non‐primary cancer death in patients treated with stereotactic body radiotherapy for pulmonary oligometastases. (6th October 2020) - Yamamoto, Takaya; Niibe, Yuzuru; Matsumoto, Yasuo; Aoki, Masahiko; Oh, Ryoong‐Jin; Ozaki, Masatoki; Kobayashi, Mitsuru; Manabe, Yoshihiko; Shintani, Takashi; Dekura, Yasuhiro; Onishi, Hiroshi; Yamashita, Hideomi; et al.
Abstract: Cancer‐specific death (CSD) and non‐cancer‐specific death (non‐CSD) after stereotactic body radiotherapy (SBRT) for pulmonary oligometastases have not been studied in detail. The aim of this study was to determine the cumulative incidences of CSD and non‐CSD and to reveal prognostic factors. Data from a large survey of SBRT for pulmonary oligometastases were used for analyses, and patients with unknown cause of death were excluded from current analyses. CSD was primary cancer death and non‐CSD was non‐primary cancer death including a series of cancer treatment‐related deaths. Cumulative incidences were calculated using the Kaplan‐Meier method and a stratified Cox regression model was used for multivariate analyses (MVA). Fifty‐two patients with an unknown death were excluded and a total of 1326 patients was selected. CSD and non‐CSD occurred in 375 and 109 patients, respectively. The median OS period was 53.2 months and the cumulative incidences of 1‐, 3‐, and 5‐year CSD vs. non‐CSD rates were 6.5% vs. 2.3%, 29.5% vs. 8.6%, and 41.2% vs. 11.0%, respectively. In MVA, the incidence of CSD was related to performance status (1 vs. 0; p < 0.001, 2–3 vs. 0; p = 0.011), oligometastatic state (sync‐oligometastases vs. oligo‐recurrence, p = 0.026) and maximum tumor diameter ( p = 0.009), and the incidence of non‐CSD was related to age ( p = 0.001), sex ( p = 0.030), performance status (2–3 vs. 0; p = 0.002), and irradiated tumor‐located lung lobe (left lower lobe vs. other lobes, p = 0.036). CSD was main cause of death, but non‐CSD was not rare after SBRT. Prognostic factors for CSD and non‐CSD were different, and an understanding of the factors would help in treatment. Abstract : The incidences cancer‐specific death and non‐cancer‐specific death after stereotactic body radiotherapy for pulmonary oligometastases were 29.5 and 8.6% at 3 years, respectively. Cancer‐specific death significantly related to performance status, oligometastatic state or disease‐free interval and maximum tumor diameter, on the other hand, non‐cancer‐specific death significantly related to age and tumor‐located lung lobe.